Alumina fiber precursor, preparation method thereof and alumina fiber
By using nano-aluminum sol, surfactants, and composite grain control agents in the preparation of alumina fiber precursors, the uniformity and strength problems of alumina fiber precursors were controlled, thus realizing the preparation of high-performance alumina fibers.
Patent Information
- Application Number
- CN202411563040.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-07
AI Technical Summary
The uniformity of the microstructure of alumina fiber precursor is difficult to control, resulting in extremely low fiber strength and a high breakage rate during the spinning process.
Nano-aluminum sol and surfactants are used as raw material components of the precursor spinning solution. By regulating the surface charge and electrostatic repulsion of aluminum particles, the aggregation of aluminum particles and the formation of chain-like structures are avoided. Combined with composite grain control agents, the nucleation and growth of alumina grains are controlled, thereby optimizing the spinning process.
This method improves the uniformity and strength of the alumina fiber precursor, reduces the breakage rate, and obtains a precursor spinning solution with high dispersibility and high stability, thus producing high-performance alumina fibers.
Smart Images

Figure CN119265751A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of alumina fibers, and in particular to an alumina fiber precursor and a preparation method thereof, and alumina fibers. Background Art
[0002] Alumina fiber is a high-performance polycrystalline inorganic fiber with advantages such as high mechanical strength, low thermal conductivity, and electrical insulation. It can maintain high strength and modulus, especially in high-temperature oxidative environments, making it the most promising ultra-light high-temperature structural material for research and development in oxidative environments. The sol-gel method is an important method for the industrial preparation of alumina fibers. First, inorganic aluminum salts or organic aluminum alcohols are selected as precursors, and a sol with uniform properties is obtained through hydrolysis / alcoholysis reactions. The sol is then aged and concentrated to form a spinnable precursor spinning solution. Alumina fiber precursors are obtained using spinning technology, and finally polycrystalline alumina fibers are obtained through different sintering processes. Among them, the quality and performance of alumina fiber precursors directly affect the uniformity of the fiber's organizational structure and the stability of its application performance.
[0003] However, there is still a lack of research on the performance of alumina fiber precursors, and the uniformity of the organizational structure of alumina fiber precursors is difficult to control, resulting in extremely low fiber precursor strength and a high fiber breakage rate during the spinning process. Summary of the invention
[0004] The present application provides an alumina fiber precursor and a preparation method thereof, and an alumina fiber to solve the following technical problem: how to improve the uniformity of the organizational structure of the alumina fiber precursor.
[0005] In a first aspect, the present application provides an alumina fiber precursor, wherein the raw material of the alumina fiber precursor includes a precursor spinning solution, and the raw material components of the precursor spinning solution include: nano aluminum sol and a surfactant; wherein:
[0006] The weight of the surfactant is 0.1% to 6.0% of the weight of the aluminum oxide in the nano aluminum sol.
[0007] Optionally, the surfactant includes at least one of the following: polyvinyl pyrrolidone, polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose, polyethylene glycol, polyethylene oxide, and polyacrylic acid.
[0008] Optionally, the raw material components of the precursor spinning solution also include: a composite grain control agent.
[0009] Optionally, the composite grain control agent includes at least two of the following: SiO 2 , CaO, MgO, Fe 2 O 3 , Y 2 O 3 、ZrO2 、Al 2 O 3 .
[0010] Optionally, the weight of the composite grain control agent is 0.1% to 18% of the weight of the aluminum oxide in the nano aluminum sol.
[0011] Optionally, the alumina fiber precursor meets the following indicators: a fineness of 1.5 dtex to 7.2 dtex, and a strength of 0.1 cN / dtex to 4.0 cN / dtex.
[0012] In a second aspect, the present application provides a method for preparing the alumina fiber precursor according to any one of the first aspects, the method comprising:
[0013] Obtaining nano aluminum sol;
[0014] The nano aluminum sol, the composite grain control agent and the surfactant are mixed to obtain a mixed material;
[0015] The mixed material is sequentially aged and concentrated to obtain a precursor spinning solution;
[0016] The precursor spinning solution is spun to obtain alumina fiber precursors.
[0017] Optionally, the step of obtaining the nano aluminum sol comprises:
[0018] The hydrated aluminum oxide and the composite carboxylic acid are subjected to a solvent thermal peptization reaction to obtain a nano aluminum sol; wherein,
[0019] The process parameters of the solvent thermal peptization reaction include: a temperature of 60° C. to 200° C., a pH value of 1.0 to 4.0; and / or, the weight of the carboxyl group of the composite carboxylic acid is 60% to 90%; and / or,
[0020] The complex carboxylic acid comprises at least two of the following: formic acid, acetic acid, lactic acid, tartaric acid, and citric acid.
[0021] Optionally, the aging temperature is 30°C to 80°C.
[0022] In a third aspect, the present application provides an alumina fiber, the raw material of the alumina fiber comprising the alumina fiber precursor described in any one of the first aspects.
[0023] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0024] The raw material of the alumina fiber precursor provided in the embodiment of the present application includes a precursor spinning solution, and the raw material components of the precursor spinning solution include: nano aluminum sol and surfactant; wherein the weight of the surfactant is 0.1% to 6.0% of the weight of aluminum oxide in the nano aluminum sol. The surfactant can be adsorbed on the surface of aluminum particles in the nano aluminum sol, thereby forming a physical barrier on the surface of the aluminum particles, and at the same time, the surface charge of the aluminum particles is regulated, and the electrostatic repulsion between the aluminum particles is enhanced, thereby preventing the contact and aggregation between the aluminum particles, thereby improving the dispersibility and stability of the nano aluminum sol; and the surfactant can induce the aluminum particles in the nano aluminum sol to aggregate to form a chain structure, avoiding the formation of a three-dimensional network structure, thereby improving the spinnability of the precursor spinning solution, and satisfying that the weight of the surfactant is 0.1% to 6.0% of the weight of aluminum oxide in the nano aluminum sol, a precursor spinning solution with high dispersibility, high uniformity and high stability can be obtained, thereby improving the uniformity of the organizational structure of the alumina fiber precursor. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0027] Figure 1 A schematic diagram of a process for preparing an alumina fiber precursor provided in an embodiment of the present application;
[0028] Figure 2 The particle size distribution diagram of the nano aluminum sol provided in Example 1 of the present application;
[0029] Figure 3 This is a SEM image of the aging of the mixture of the nano aluminum sol, the composite grain control agent and the surfactant provided in Example 1 of the present application;
[0030] Figure 4 This is a SEM image of the alumina fiber precursor provided in Example 1 of the present application;
[0031] Figure 5 The tensile curve of the alumina fiber precursor provided in Example 1 of the present application;
[0032] Figure 6 This is a SEM image of the alumina fiber provided in Example 1 of the present application;
[0033] Figure 7 This is the tensile curve of the alumina fiber provided in Example 1 of the present application. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0035] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0036] In this document, the terms including "include" and the like mean "including but not limited to". "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; wherein A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, wherein a, b, and c can be single or plural, respectively.
[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0038] Alumina precursor sol can be divided into organic system, inorganic system, organic-inorganic mixed system. Due to the complex formation process of sol, the composition and structure of aluminum particles in sol are significantly different. During the sol concentration process, these aluminum particles will aggregate to form secondary particles or larger aggregates. The inhomogeneity of the aggregate structure leads to poor spinnability of the sol, so a large amount of spinning aids must be used to improve the spinning quality. Although the surface quality of alumina fiber precursor has been improved, the internal structure is not easy to control, resulting in extremely low fiber precursor strength and high fiber breakage rate during the spinning process. So far, there is still a blank in the research on the performance of alumina fiber precursor. The performance of alumina fiber precursor is not only related to the spinnability of the sol, but also to the uniformity and cross-linking degree of the sol aggregate. It is not comprehensive to measure the performance of the fiber precursor by the spinning length and surface quality of the alumina fiber precursor. The preparation of alumina fiber precursor with uniform organizational structure and excellent mechanical properties has become the key to the preparation of high-performance alumina fiber. Therefore, the poor uniformity of the original structure of alumina fibers and extremely low strength are urgent problems to be solved in the field of alumina fibers.
[0039] Therefore, in a first aspect, the present application provides an alumina fiber precursor, wherein the raw material of the alumina fiber precursor includes a precursor spinning solution, and the raw material components of the precursor spinning solution include: nano aluminum sol and a surfactant; wherein,
[0040] The weight of the surfactant is 0.1% to 6.0% of the weight of the aluminum oxide in the nano aluminum sol.
[0041] In the embodiment of the present application, the nano-alumina sol is a colloidal solution in which positively charged hydrated alumina particles are uniformly dispersed in water. The nano-alumina sol has a nano-scale size, a large specific surface area, stability and dispersibility, and can give the precursor spinning solution high dispersibility and high activity, thereby improving the stability of the spinning process and the performance of the alumina fiber precursor. The surfactant can be adsorbed on the surface of the aluminum particles in the nano-aluminum sol, thereby forming a physical barrier on the surface of the aluminum particles, and at the same time regulating the surface charge of the aluminum particles, enhancing the electrostatic repulsion between the aluminum particles, thereby preventing the contact and aggregation between the aluminum particles, and thus improving the dispersibility and stability of the nano-aluminum sol; and the surfactant can induce the aluminum particles in the nano-aluminum sol to aggregate to form a chain structure, avoiding the formation of a three-dimensional network structure, thereby improving the spinnability of the precursor spinning solution, and the weight of the surfactant can be 0.1% to 6.0% of the weight of the aluminum oxide in the nano-aluminum sol, thereby improving the dispersibility and stability of the nano-aluminum sol, inducing the aluminum particle aggregates in the nano-aluminum sol to form a longer chain structure, improving the spinnability of the precursor spinning solution, and then obtaining a precursor spinning solution with high dispersibility, high uniformity and high stability, and improving the uniformity of the organizational structure of the aluminum oxide fiber precursor. If the weight of the surfactant is higher than 6.0% of the weight of the aluminum oxide in the nano-aluminum sol, a large number of pores will be formed in the subsequent aluminum oxide fiber to a certain extent, making it difficult to densify the aluminum oxide fiber; if the weight of the surfactant is lower than 0.1% of the weight of the aluminum oxide in the nano-aluminum sol, it is difficult to improve the uniformity of the organizational structure of the aluminum oxide fiber precursor to a certain extent. Exemplarily, the weight of the above-mentioned surfactant can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, etc. of the weight of the aluminum oxide in the nano-aluminum sol.
[0042] In some embodiments, the surfactant includes at least one of polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), hydroxyethyl cellulose (HEC), polyethylene glycol (PEG), polyethylene oxide (PEO), and polyacrylic acid (PAA).
[0043] In an embodiment of the present application, the surfactant may be a combination of one or more of polyvinyl pyrrolidone, polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose, polyethylene glycol, polyethylene oxide, and polyacrylic acid.
[0044] In some embodiments, the raw material components of the precursor spinning solution also include: a composite grain control agent.
[0045] In the embodiment of the present application, the raw material components of the precursor spinning solution also include: a composite grain control agent. The grain control agent can control the nucleation and growth of alumina grains, so that the organizational structure of the alumina grains remains stable, and the abnormal growth of the grains is avoided, thereby affecting the density and mechanical properties of the fiber. Compared with a single grain control agent, the composite grain control agent can simultaneously take into account the regulation of the size of the alumina grains and the density of the alumina fiber.
[0046] In some embodiments, the composite grain control agent includes at least two of the following: SiO 2 , CaO, MgO, Fe 2 O 3 , Y 2 O 3 、ZrO 2 、Al 2 O 3 .
[0047] In the embodiment of the present application, the composite grain control agent may be SiO 2 , CaO, MgO, Fe 2 O 3 , Y 2 O 3 、ZrO 2 、Al 2 O 3 In the combination of two or more of the above, these grain control agents can be used as nucleating agents for alumina grains, improve the nucleation rate, and refine the organization of alumina fibers; the grain control agent can form a low eutectic point system with alumina, which is conducive to the densification of alumina fibers; and the grain control agent can react with alumina to form a new organization, inhibit the abnormal growth of alumina grains, and improve the stability of the fiber organization structure. In addition, the composite grain control agent is an oxide, which can optimize the subsequent sintering process of alumina fiber precursors, improve the purity and organization structure uniformity of alumina fibers, avoid side reactions, and thus reduce impurities in the fibers. The appearance of the grain control agent can be a nano powder or a colloidal aqueous dispersion.
[0048] In some embodiments, the weight of the composite grain control agent is 0.1% to 18% of the weight of the aluminum oxide in the nano aluminum sol.
[0049] In the embodiment of the present application, the weight of the composite grain control agent can be 0.1% to 18% of the weight of the alumina in the nano-alumina sol, so as to fully realize the control of the nucleation and growth of the alumina grains, thereby obtaining alumina fibers with fine, dense and uniform organizational structure. If the weight of the composite grain control agent is higher than 18% of the weight of the alumina in the nano-alumina sol, it will be difficult to obtain densified alumina fibers by subsequent sintering of the alumina fiber precursor to a certain extent; if the weight of the composite grain control agent is lower than 0.1% of the weight of the alumina in the nano-alumina sol, it will be difficult to realize the control of the nucleation and growth of the alumina grains to a certain extent. Exemplarily, the weight of the composite grain control agent can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, etc., of the weight of alumina in the nano aluminum sol.
[0050] In some embodiments, the alumina fiber precursor meets the following indicators: a fineness of 1.5 dtex to 7.2 dtex, and a strength of 0.1 cN / dtex to 4.0 cN / dtex.
[0051] In the embodiments of the present application, the above-mentioned alumina fiber precursor has a relatively uniform tissue structure and very high strength, which solves the problem of poor uniformity of the fiber precursor and a high wire breakage rate.
[0052] In a second aspect, the present application provides a method for preparing the alumina fiber precursor according to any one of the first aspects, Figure 1 A schematic diagram of a process for preparing an alumina fiber precursor provided in an embodiment of the present application; see Figure 1 , the method comprising:
[0053] S1, obtaining nano aluminum sol;
[0054] In some embodiments, the step of obtaining the nano aluminum sol comprises:
[0055] The hydrated aluminum oxide and the composite carboxylic acid are subjected to a solvent thermal peptization reaction to obtain a nano aluminum sol; wherein,
[0056] The process parameters of the solvent thermal peptization reaction include: a temperature of 60° C. to 200° C., a pH value of 1.0 to 4.0; and / or, the weight of the carboxyl group of the composite carboxylic acid is 60% to 90%; and / or,
[0057] The complex carboxylic acid comprises at least two of the following: formic acid, acetic acid, lactic acid, tartaric acid, and citric acid.
[0058] In the present embodiment, hydrated alumina is an aluminum oxide compound containing crystal water, and its general chemical formula can be expressed as (Al 2 O 3 ·nH 2 O, 0.5≤n≤6). The hydrated aluminum oxide may be a combination of one or more of pseudo-boehmite, boehmite, and aluminum hydroxide. As an embodiment of step S1, it specifically comprises: 2 O 3 ·nH 2 O, 0.5≤n≤6) to make a slurry, add a carboxylic acid solution to adjust the pH of the slurry, perform a solvent thermal peptization reaction at a temperature of 60°C to 200°C, and then filter and centrifuge the reaction product to obtain a nano aluminum sol. The solid phase weight of the slurry can be 5% to 30% (in terms of Al 2 O 3 count).
[0059] Carboxylic acid provides an acidic environment in the solvent peptization reaction and reacts with hydrated alumina to form nano-alumina sol; in the preparation stage of the precursor spinning solution, on the one hand, the active sites of the aluminum particles coordinate with the carboxylic acid molecules, which is conducive to the formation of a chain structure of the aluminum particles, thereby improving the spinnability of the precursor spinning solution; on the other hand, the Al-OH group on the surface of the aluminum particles condenses with the -COOH group of the carboxylic acid molecule to form a strong cross-linked Al-OC structure. This chemical connection is conducive to improving the strength of the alumina fiber precursor. Different carboxylic acids have different chemical structures and properties, and their modes of action with hydrated alumina may also be different. Therefore, by using composite carboxylic acids, their synergistic effects can be exerted to improve the peptization effect on hydrated alumina. The carboxyl groups in the carboxylic acid structure are ionized to generate hydrogen ions in the solvent, and the hydrogen ions react with the hydroxyl groups on the surface of the hydrated aluminum oxide to generate an aluminum-carboxylic acid complex. In addition, the carboxyl groups in the carboxylic acid structure can replace the hydroxyl groups on the surface of the hydrated aluminum oxide, and react with the aluminum ions to generate an aluminum-carboxylic acid complex. The aluminum-carboxylic acid complex is formed on the surface of the aluminum particles, so that the aluminum particles are charged, thereby generating an electrostatic repulsion effect to prevent the aluminum particles from agglomerating, so that the aluminum particles can stably exist in the solvent to form a nano-aluminum sol. The carboxyl groups and the hydroxyl groups on the surface of the hydrated aluminum oxide can form hydrogen bonds, thereby increasing the contact opportunities between the hydrated aluminum oxide and the composite carboxylic acid molecules, promoting the acid-base reaction and the ligand exchange reaction, and thus promoting the formation of the nano-aluminum sol.
[0060] The process parameters of the above solvent thermal peptization reaction include: the temperature can be 60°C to 200°C, the pH value can be 1.0 to 4.0, and the reaction is sufficient to generate a stable nano aluminum sol. Exemplarily, the temperature can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.; the pH value can be 1.0, 2.0, 3.0, 4.0, etc. In addition, the time of the solvent thermal peptization reaction can be 2h to 24h.
[0061] The weight of the carboxyl group of the composite carboxylic acid can be 60% to 90%. From the reaction mechanism of hydrated alumina and carboxylic acid, it can be seen that the solvent thermal peptization reaction mainly depends on the ionization constant of the carboxylic acid and the number of hydroxyl groups, and the ionization constant of the carboxylic acid is also related to the hydroxyl group. Therefore, the appropriate carboxyl ratio in the carboxylic acid plays an important positive role in the solvent thermal peptization reaction and the precursor spinning solution. Exemplarily, the weight of the carboxyl group in the composite carboxylic acid can be 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc. The composite carboxylic acid can be a combination of two or more of formic acid, acetic acid, lactic acid, tartaric acid, and citric acid.
[0062] S2, mixing the nano aluminum sol, the composite grain control agent and the surfactant to obtain a mixed material;
[0063] In the embodiments of the present application, the grain control agent and the aluminum particles in the nano-aluminum sol can fully contact to form a uniformly dispersed sol system, and the surfactant is adsorbed on the surface of the aluminum particles and the grain control agent to form a physical barrier, while adjusting their surface charge, increasing the electrostatic repulsion between the aluminum particles, and preventing contact and aggregation between the aluminum particles, thereby improving the dispersion characteristics of the grain control agent and the aluminum particles, and further improving the spinnability of the precursor spinning solution.
[0064] S3, aging and concentrating the mixed material in sequence to obtain a precursor spinning solution;
[0065] In some embodiments, the aging temperature is 30°C to 80°C.
[0066] In the embodiment of the present application, the aging temperature can be 30°C to 80°C. Aging can make the aluminum particles of the nano-aluminum sol fully react with the surfactant. Under the action of the surfactant, the aluminum particles aggregate and connect to each other to form a linear structure. It is also beneficial to the subsequent concentration process to regulate the aggregation mode of the aluminum particles, induce the aluminum particle aggregates to form a longer chain structure, and avoid abnormal or excessive agglomeration of aluminum particles, thereby obtaining a uniform aluminum particle aggregate. Therefore, after aging and concentration, a spinnable precursor spinning solution is obtained. Exemplarily, the above-mentioned aging temperature can be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 70°C, 75°C, 80°C, etc. In addition, the aging time can be 10h to 48h.
[0067] S4, spinning the precursor spinning solution to obtain alumina fiber precursor.
[0068] In the embodiment of the present application, the above spinning process parameters may include: the length of the spinning tunnel is 1m to 10m; the environmental parameters of the spinning tunnel are as follows: the wind speed is 0.1m / s to 1m / s, the temperature is 20℃ to 150℃, and the humidity is 20% to 70%. The precursor spinning solution enters the spinning tunnel from the micropores of the spinneret, and is dried and stretched in the spinning tunnel to obtain alumina fiber precursor. Under the action of the above spinning process parameters, the spinning environment can be optimized, the volatilization rate of the solvent can be controlled, and the spinning process can be made more stable and continuous, thereby obtaining uniform alumina fiber precursor.
[0069] The preparation method of the alumina fiber precursor is realized based on the above-mentioned alumina fiber precursor. The specific raw materials of the alumina fiber precursor can refer to the above-mentioned embodiments. Since the preparation method of the alumina fiber precursor adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0070] In a third aspect, the present application provides an alumina fiber, the raw material of the alumina fiber comprising the alumina fiber precursor described in any one of the first aspects.
[0071] In the embodiment of the present application, the alumina fiber is prepared from the above-mentioned alumina fiber precursor as a raw material. The fineness of the alumina fiber (single fiber) is 3.1 dtex to 5.0 dtex, and the strength is 5 cN / dtex to 12 cN / dtex.
[0072] The alumina fiber is realized based on the above-mentioned alumina fiber precursor. The specific raw materials of the alumina fiber precursor can refer to the above-mentioned embodiments. Since the alumina fiber adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0073] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for the unrecorded specific conditions in the following examples are usually measured according to national standards. If there is no corresponding national standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.
[0074] Example 1
[0075] Alumina fiber precursor, the raw material of which includes a precursor spinning solution, the raw material components of which include: nano aluminum sol, a surfactant and a composite grain control agent; wherein:
[0076] The weight of the surfactant is 1.4% of the weight of the aluminum oxide in the nano aluminum sol; the surfactant includes PVP and PEO;
[0077] The weight of the composite grain control agent is 1.6% of the weight of the aluminum oxide in the nano aluminum sol; the composite grain control agent comprises silica sol, CaO and MgO with a solid phase weight of 30%.
[0078] A method for preparing alumina fiber precursor comprises the following steps:
[0079] (1) Preparation of Nano-aluminum Sol
[0080] 500g pseudo-boehmite (Al 2 O 3 The solid phase weight of the slurry is 15% (with Al 2 O 3 To the slurry, a composite carboxylic acid (carboxyl weight is 84.6%, 50g formic acid, 54g acetic acid and 10g citric acid) is added to control the pH at 2.1. The solvent thermal peptization reaction is carried out at 80°C for 4h. The sol is then filtered and centrifuged to obtain a uniformly dispersed nano aluminum sol.
[0081] (2) Precursor spinning solution
[0082] To the nano-aluminum sol obtained in step (1), add 8 g of silica sol with a solid phase weight of 30%, 1.6 g of CaO, and 0.8 g of MgO, stir and mix evenly, then add 3.1 g of PVP and 1.2 g of PEO, mix and age at 45° C. for 24 hours, and then concentrate to obtain a spinnable precursor spinning solution.
[0083] (3) Alumina fiber precursor
[0084] The precursor spinning solution obtained in step (2) is spun on a dry spinning device with a spinning tunnel length of 4 m and tunnel environmental parameters of wind speed 0.3 m / s, temperature 85°C, and humidity 55%. The alumina fiber precursor is obtained by bundling at 150 m / min.
[0085] The fineness of the alumina fiber precursor is 2.65 dtex and the strength is 3.22 cN / dtex.
[0086] The alumina fiber precursor obtained above was continuously sintered to obtain alumina fiber, and the fiber fineness was 3.91 dtex and the strength was 9.90 cN / dtex.
[0087] For example, Figure 2 The particle size distribution diagram of the nano aluminum sol provided in Example 1 of the present application; see Figure 2 , indicating that the particle size distribution of aluminum sol is unimodal, and its particle size distribution is extremely concentrated and uniform, with an average particle size of 11.7nm; Figure 3 This is a SEM image of the aging of the mixture of nano aluminum sol, composite grain control agent and surfactant provided in Example 1 of the present application; see Figure 3 , indicating that after aging, the aluminum particles in the mixture aggregate to form aggregates of about 60 to 90 nm, and these aggregates are interconnected to form a linear structure, which has a positive effect on improving the spinnability of the spinning solution and the uniformity of the alumina fiber precursor; Figure 4 This is the SEM image of the alumina fiber precursor provided in Example 1 of the present application; see Figure 4 , indicating that the size of the alumina fiber precursor is about 15 μm, and the surface is smooth and crack-free; Figure 5 This is the tensile curve of the alumina fiber precursor provided in Example 1 of the present application; see Figure 5 , indicating that the breaking strength of the alumina fiber precursor is as high as 8.53 cN; Figure 6 SEM image of alumina fiber provided in Example 1 of the present application; see Figure 6 , indicating that the size of alumina fibers is around 11 μm; Figure 7 The tensile curve of the alumina fiber provided in Example 1 of the present application; see Figure 7 , indicating that the breaking strength of alumina fiber is 38.70 cN.
[0088] Example 2
[0089] Alumina fiber precursor, the raw material of which includes a precursor spinning solution, the raw material components of which include: nano aluminum sol, a surfactant and a composite grain control agent; wherein:
[0090] The weight of the surfactant is 0.8% of the weight of the aluminum oxide in the nano aluminum sol; the surfactant includes PVP and PVA;
[0091] The weight of the composite grain control agent is 1.1% of the weight of the aluminum oxide in the nano aluminum sol; the composite grain control agent includes a solid phase weight of 30% silica sol, Fe 2 O 3 .
[0092] A method for preparing alumina fiber precursor comprises the following steps:
[0093] (1) Preparation of Nano-aluminum Sol
[0094] 500g boehmite (Al 2 O 3 The solid phase weight of the slurry is 17% (with Al 2 O 3 To the slurry (the weight of carboxyl group is 84.8%, including 46g formic acid, 50g acetic acid and 5g tartaric acid) was added a complex carboxylic acid (the weight of carboxyl group is 84.8%, including 46g formic acid, 50g acetic acid and 5g tartaric acid) so that the pH of the slurry was controlled at 1.7. At 110°C, the solvent was thermally peptized for 8h. Then, the sol was filtered and centrifuged to obtain a uniformly dispersed nano aluminum sol.
[0095] (2) Precursor spinning solution
[0096] To the nano-aluminum sol obtained in step (1), 8 g of silica sol with a solid phase weight of 30% and 1.8 g of Fe 2 O 3 , stir and mix evenly, then add 2.6g PVP and 0.4g PVA, mix and age at 60°C for 20h, and then concentrate to obtain a spinnable precursor spinning solution.
[0097] (3) Alumina fiber precursor
[0098] The precursor spinning solution obtained in step (2) is spun on a dry spinning device with a spinning tunnel length of 3 m and tunnel environmental parameters of wind speed 0.3 m / s, temperature 90°C, and humidity 45%. The alumina fiber precursor is obtained by bundling at 100 m / min.
[0099] The fineness of the alumina fiber precursor is 3.47 dtex and the strength is 2.18 cN / dtex.
[0100] The alumina fiber precursor obtained above was continuously sintered to obtain alumina fiber, and the fiber fineness was 4.09 dtex and the strength was 8.55 cN / dtex.
[0101] Example 3
[0102] Alumina fiber precursor, the raw material of which includes a precursor spinning solution, the raw material components of which include: nano aluminum sol, a surfactant and a composite grain control agent; wherein:
[0103] The weight of the surfactant is 2.5% of the weight of the aluminum oxide in the nano aluminum sol; the surfactant includes CMC and PAA;
[0104] The weight of the composite grain control agent is 1.4% of the weight of the aluminum oxide in the nano aluminum sol; the composite grain control agent comprises silica sol, CaO and MgO with a solid phase weight of 30%.
[0105] A method for preparing alumina fiber precursor comprises the following steps:
[0106] (1) Preparation of Nano-aluminum Sol
[0107] 500g aluminum hydroxide (Al 2 O 3 The solid phase weight of the slurry is 12% (with Al 2 O 3 To the slurry (the weight of carboxyl group is 85.3%, including 50g formic acid, 30g acetic acid and 9g lactic acid), a complex carboxylic acid (the weight of carboxyl group is 85.3%, including 50g formic acid, 30g acetic acid and 9g lactic acid) is added to control the pH of the slurry at 2.4, and the solvent thermal peptization reaction is carried out at 145°C for 6h, and then the sol is filtered and centrifuged to obtain a uniformly dispersed nano aluminum sol.
[0108] (2) Precursor spinning solution
[0109] To the nano-aluminum sol obtained in step (1), add 6 g of silica sol with a solid phase weight of 30%, 1.5 g of CaO, and 1.0 g of MgO, and after stirring and mixing evenly, add 6.8 g of CMC and 1.2 g of PAA, mix and age at 50° C. for 30 h, and then concentrate to obtain a spinnable precursor spinning solution.
[0110] (3) Alumina fiber precursor
[0111] Same as Example 1.
[0112] The fineness of the alumina fiber precursor is 3.08 dtex and the strength is 2.64 cN / dtex.
[0113] The alumina fiber precursor obtained above was continuously sintered to obtain alumina fiber, and the fiber fineness was 4.16 dtex and the strength was 8.19 cN / dtex.
[0114] Example 4
[0115] An alumina fiber precursor, same as that in Example 1.
[0116] A method for preparing alumina fiber precursor comprises the following steps:
[0117] (1) Preparation of Nano-aluminum Sol
[0118] 500g pseudo-boehmite (Al 2 O 3 The solid phase weight of the slurry is 15% (with Al 2 O 3 To the slurry (the weight of carboxyl group is 75.5%, including 23g formic acid, 50g propionic acid and 9g lactic acid), a complex carboxylic acid is added so that the pH of the slurry is controlled at 1.5. At 105°C, the solvent is thermally peptized for 7h. The sol is then filtered and centrifuged to obtain a uniformly dispersed nano aluminum sol.
[0119] (2) Precursor spinning solution
[0120] Same as Example 1.
[0121] (3) Alumina fiber precursor
[0122] Same as Example 1.
[0123] The fineness of the alumina fiber precursor is 2.93 dtex and the strength is 2.68 cN / dtex.
[0124] The alumina fiber precursor obtained above was continuously sintered to obtain alumina fiber, and the fiber fineness was 4.05 dtex and the strength was 9.12 cN / dtex.
[0125] Example 5
[0126] Alumina fiber precursor, the raw material of which includes a precursor spinning solution, the raw material components of which include: nano aluminum sol, a surfactant and a composite grain control agent; wherein:
[0127] The weight of the surfactant is 1.7% of the weight of the aluminum oxide in the nano aluminum sol; the surfactant includes PVP and HEC;
[0128] The weight of the composite grain control agent is 8.6% of the weight of the aluminum oxide in the nano aluminum sol; the composite grain control agent includes a solid phase weight of 30% silica sol, Fe 2 O 3 and MgO.
[0129] A method for preparing alumina fiber precursor comprises the following steps:
[0130] (1) Preparation of Nano-aluminum Sol
[0131] Same as Example 1.
[0132] (2) Precursor spinning solution
[0133] To the nano-aluminum sol obtained in step (1), 80 g of silica sol with a solid phase weight of 30%, 1.79 g of Fe 2 O 3 , 0.8g MgO, stir and mix evenly, then add 3.6g PVP and 1.4g HEC, mix and age at 50°C for 18h, and then concentrate to obtain a spinnable precursor spinning solution.
[0134] (3) Alumina fiber precursor
[0135] The precursor spinning solution obtained in step (2) is spun on a dry spinning device with a spinning tunnel length of 5 m and tunnel environmental parameters of wind speed 0.5 m / s, temperature 95°C, and humidity 65%. The alumina fiber precursor is obtained by bundling at 120 m / min.
[0136] The fineness of the alumina fiber precursor is 3.02 dtex and the strength is 2.47 cN / dtex.
[0137] The alumina fiber precursor obtained above was continuously sintered to obtain alumina fiber, and the fiber fineness was 4.17 dtex and the strength was 8.23 cN / dtex.
[0138] Example 6
[0139] Alumina fiber precursor, the raw material of which includes a precursor spinning solution, the raw material components of which include: nano aluminum sol, a surfactant and a composite grain control agent; wherein:
[0140] The weight of the surfactant is 2.0% of the weight of the aluminum oxide in the nano aluminum sol; the surfactant includes PVP and PEO;
[0141] The weight of the composite grain control agent is 12.3% of the weight of the aluminum oxide in the nano aluminum sol; the composite grain control agent includes zirconium sol with a solid phase weight of 20%, Y 2 O 3 and MgO.
[0142] A method for preparing alumina fiber precursor comprises the following steps:
[0143] (1) Preparation of Nano-aluminum Sol
[0144] Same as Example 2
[0145] (2) Precursor spinning solution
[0146] To the nano-aluminum sol obtained in step (1), 200 g of zirconium sol with a solid phase weight of 20%, 5.0 g of Y 2 O 3 , 4.2gMgO was stirred and mixed evenly, and then 6.7gPVP and 1.2gPEO were added thereto. After mixing, the mixture was aged at 55°C for 30h and then concentrated to obtain a spinnable precursor spinning solution.
[0147] (3) Alumina fiber precursor
[0148] The precursor spinning solution obtained in step (2) is spun on a dry spinning device with a spinning tunnel length of 3 m and tunnel environmental parameters of wind speed 0.25 m / s, temperature 80°C, and humidity 45%. The alumina fiber precursor is obtained by bundling at 120 m / min.
[0149] The fineness of the alumina fiber precursor is 4.41 dtex and the strength is 1.57 cN / dtex.
[0150] The alumina fiber precursor obtained above was continuously sintered to obtain alumina fiber, and the fiber fineness was 4.65 dtex and the strength was 6.73 cN / dtex.
[0151] Example 7
[0152] Alumina fiber precursor, the raw material of which includes a precursor spinning solution, the raw material components of which include: nano aluminum sol, a surfactant and a composite grain control agent; wherein:
[0153] The weight of the surfactant is 2.2% of the weight of the aluminum oxide in the nano aluminum sol; the surfactant includes HEC and PAA;
[0154] The weight of the composite grain control agent is 3.2% of the weight of the aluminum oxide in the nano aluminum sol; the composite grain control agent includes a solid phase weight of 30% of silica sol, Y 2 O 3 and MgO.
[0155] A method for preparing alumina fiber precursor comprises the following steps:
[0156] (1) Preparation of Nano-aluminum Sol
[0157] 500g aluminum hydroxide (Al 2 O 3 The solid phase weight of the slurry is 12% (with Al 2 O 3To the slurry (the weight of carboxyl group is 74.5%, including 30g formic acid, 50g propionic acid and 5g citric acid), the pH of the slurry is controlled at 1.9, and the solvent thermal peptization reaction is carried out at 130°C for 8h, and then the sol is filtered and centrifuged to obtain a uniformly dispersed nano aluminum sol.
[0158] (2) Precursor spinning solution
[0159] To the nano-aluminum sol obtained in step (1), 6 g of silica sol with a solid phase weight of 30% and 6.4 g of Y 2 O 3 , 2.1gMgO, stir and mix evenly, then add 5.4gHEC and 1.5gPAA, mix and age at 55°C for 24h, and then concentrate to obtain a spinnable precursor spinning solution.
[0160] (3) Alumina fiber precursor
[0161] The precursor spinning solution obtained in step (2) is spun on a dry spinning device with a spinning tunnel length of 5 m and tunnel environmental parameters of wind speed 0.45 m / s, temperature 75°C, and humidity 50%. The alumina fiber precursor is obtained by bundling at 100 m / min.
[0162] The fineness of the alumina fiber precursor is 4.32 dtex and the strength is 1.72 cN / dtex.
[0163] The alumina fiber precursor obtained above was continuously sintered to obtain alumina fiber, and the fiber fineness was 4.41 dtex and the strength was 6.59 cN / dtex.
[0164] Comparative Example 1
[0165] Based on the disclosure of Example 1, the difference between Comparative Example 1 and Example 1 is that:
[0166] There is no surfactant in the precursor spinning solution.
[0167] Results: Since no surfactant was added to the precursor spinning solution, the aggregation behavior of aluminum particles changed significantly. The aggregates gradually changed from a linear structure to a three-dimensional network structure, and the precursor spinning solution became a thixotropic fluid, that is, its fluidity changed significantly with time and shear force, and thus lost its spinnability.
[0168] Comparative Example 2
[0169] Based on the disclosure of Example 1, the difference between Comparative Example 2 and Example 1 is that:
[0170] The weight of the surfactant is 0.07% of the weight of the aluminum oxide in the nano aluminum sol.
[0171] Results: Due to the small amount of surfactant added in the precursor spinning solution, although the precursor spinning solution has a certain spinnability, the spinning process cannot be continuous, the fiber breakage rate is still high, and the obtained alumina fiber precursor has no strength.
[0172] Comparative Example 3
[0173] Based on the disclosure of Example 1, the difference between Comparative Example 3 and Example 1 is that:
[0174] The weight of the surfactant is 7.0% of the weight of the aluminum oxide in the nano aluminum sol.
[0175] Results: Alumina precursor sol can be spun continuously, and the obtained alumina fiber precursor has a fineness of 2.44 dtex and a strength of 1.87 cN / dtex. However, after the alumina fiber precursor is sintered, a large number of pores appear in the fiber and the fiber has no strength.
[0176] Comparative Example 4
[0177] Based on the disclosure of Example 1, the difference between Comparative Example 4 and Example 1 is that:
[0178] The precursor spinning solution contains a single grain control agent.
[0179] Results: The fineness of the obtained alumina fiber precursor was 2.81 dtex and the strength was 2.63 cN / dtex. However, after the alumina fiber precursor was sintered, abnormally grown alumina tissue appeared in the fiber and the fiber had no strength.
[0180] Comparative Example 5
[0181] Based on the disclosure of Example 1, the difference between Comparative Example 5 and Example 1 is that:
[0182] Pseudoboehmite and complex carboxylic acid did not undergo solvent thermal peptization reaction, but only condensed and refluxed at 80°C.
[0183] Results: Since the aluminum sol did not react under high temperature and high pressure, the aluminum particles in the sol showed a multi-peak distribution characteristic, and there were great differences in the size, shape and structure of the aluminum particles; the spinnability of the precursor spinning solution was poor, the broken rate of the alumina fiber precursor was high, the fineness of the obtained alumina fiber precursor was 6.7 dtex, and the precursor had no strength.
[0184] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:
[0185] (1) Surfactants can regulate the charge density on the surface of aluminum particles in nano-aluminum sol, thereby controlling the degree of aggregation of aluminum particles, avoiding the formation of a three-dimensional network structure, and improving the uniformity of the sol;
[0186] (2) The composite carboxylic acid undergoes an acid-base reaction and a coordination exchange reaction with hydrated aluminum oxide, promoting the formation of an aluminum-carboxylic acid complex, thereby obtaining a stable nano-aluminum sol;
[0187] (3) Through the interaction between surfactants and aluminum particles, the polymerization process of aluminum particles is effectively controlled. By introducing a composite grain control agent, the precursor spinning solution exhibits relatively good spinning stability and continuity. The surface of the obtained alumina fiber precursor has no obvious defects, the organizational structure is very uniform, and the strength of the fiber precursor is significantly improved.
[0188] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. An alumina fiber precursor, wherein the raw material of the alumina fiber precursor comprises a precursor spinning solution, and the raw material components of the precursor spinning solution include: Nano aluminum sol and surfactant; wherein, The weight of the surfactant is 0.1% to 6.0% of the weight of the aluminum oxide in the nano aluminum sol.
2. The alumina fiber precursor according to claim 1, characterized in that: The surfactant includes at least one of the following: polyvinyl pyrrolidone, polyvinyl alcohol, carboxymethyl cellulose, hydroxyethyl cellulose, polyethylene glycol, polyethylene oxide, and polyacrylic acid.
3. The alumina fiber precursor according to claim 1, characterized in that: The raw material components of the precursor spinning solution also include: a composite grain control agent.
4. The alumina fiber precursor according to claim 3, characterized in that: The composite grain control agent includes at least two of the following: SiO2, CaO, MgO, Fe2O3, Y2O3, ZrO2, and Al2O3.
5. The alumina fiber precursor according to claim 3 or 4, characterized in that: The weight of the composite grain control agent is 0.1% to 18% of the weight of the aluminum oxide in the nano aluminum sol.
6. The alumina fiber precursor according to claim 1, characterized in that: The alumina fiber precursor meets the following indicators: a fineness of 1.5 dtex to 7.2 dtex, and a strength of 0.1 cN / dtex to 4.0 cN / dtex.
7. A method for preparing alumina fiber precursor according to any one of claims 1 to 6, characterized in that: The method comprises: Obtaining nano aluminum sol; The nano aluminum sol, the composite grain control agent and the surfactant are mixed to obtain a mixed material; The mixed material is sequentially aged and concentrated to obtain a precursor spinning solution; The precursor spinning solution is spun to obtain alumina fiber precursors.
8. The method according to claim 7, characterized in that The method for obtaining the nano aluminum sol comprises: The hydrated aluminum oxide and the composite carboxylic acid are subjected to a solvent thermal peptization reaction to obtain a nano aluminum sol; wherein, The process parameters of the solvent thermal peptization reaction include: temperature of 60°C to 200°C, pH value of 1.0 to 4.0; and / or, The weight of carboxyl groups of the composite carboxylic acid is 60% to 90%; and / or, The complex carboxylic acid comprises at least two of the following: formic acid, acetic acid, lactic acid, tartaric acid, and citric acid.
9. The method according to claim 7, characterized in that: The aging temperature is 30°C to 80°C.
10. An alumina fiber, characterized in that: The raw material of the alumina fiber includes the alumina fiber precursor according to any one of claims 1 to 6.
Citation Information
Cited By
Alumina fiber precursor and preparation method therefor, and alumina fiber
WO2026098497A1